2016
DOI: 10.1111/jmft.12202
|View full text |Cite
|
Sign up to set email alerts
|

Global Mental Health in Action: Reducing Disparities One Community at a Time

Abstract: There are great disparities in mental health care around the world. Traditional approaches to mental health care have not been found to be transferrable to many parts of the world and are inadequate to address these disparities. Unconventional approaches are needed that match the traditions of care-seeking and care-giving within the communities where they are delivered. The authors review the global mental health literature and discuss how marriage and family therapists are in a particularly good position to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…has been crucial in recent innovative approaches aiming at improving mental health in local communities (see also Dalai in this issue). This "global mental health" practice, while respecting cultural diversity and context characteristics, assures equal access to mental health services, equity in distribution of resources and focus on treatment outcome (Bischoff et al 2016). The Reducing Mental Health Disparities One Community at a Time (RD1CT) model offers an example of integration of conventional and unconventional mental health practices that include nonprofessional members of the local community working together with mental health professionals and researchers (ibid.).…”
Section: E-mental Healthmentioning
confidence: 99%
“…has been crucial in recent innovative approaches aiming at improving mental health in local communities (see also Dalai in this issue). This "global mental health" practice, while respecting cultural diversity and context characteristics, assures equal access to mental health services, equity in distribution of resources and focus on treatment outcome (Bischoff et al 2016). The Reducing Mental Health Disparities One Community at a Time (RD1CT) model offers an example of integration of conventional and unconventional mental health practices that include nonprofessional members of the local community working together with mental health professionals and researchers (ibid.).…”
Section: E-mental Healthmentioning
confidence: 99%
“…One indicated that, “ Too few studies have attempted to understand couple therapy for gay and lesbian couples. This study fills a substantial gap and shows strong support for the Gottman approach to gay and lesbian couples .” Finally, Global Mental Health in Action: Reducing Disparities One Community at a Time by authors Richard J. Bischoff, Paul R. Springer, and Nathan Taylor received an Honorable mention. In words of one council member, this article is “ by far the most relevant article with regards to social justice.…”
Section: Article and Reviewers Of The Yearmentioning
confidence: 99%
“…Although family therapy and family therapists are not referenced in the GMH literature, family therapists have not been silent about family therapy abroad. Books and articles on global perspectives on family therapy and special issues on international family therapy have been published (Bischoff, Springer, & Taylor, 2016;Crane, 2013;Gould & DeMuth, 1993;Mehta & Thornicroft, 2014;Ng, 2014;Prince, 2014;Roberts et al, 2014). Family therapists have explored the needs of refugee and immigrant families in the United States, and family therapy educators have been active in training students abroad (Sveaass & Richelt, 2001;Weine, 2011).…”
Section: Family Therapy and Global Mental Healthmentioning
confidence: 99%